Comparative ecologies of domestic and naturalised rainbow trout in northern Lake Huron. Issue 3 (2nd May 2014) - Johnston, Tom A.; Wilson, Chris C.
Abstract Northern Lake Huron (Ontario, Canada) supports the largest concentration of freshwater salmonid cage culture farms in Canada and receives inputs of domestic‐strain rainbow trout (Oncorhynchus mykiss) through escapement. We assessed the potential effects of these domestic fish on the naturalised rainbow trout of this ecosystem by comparing their respective ecologies. Mature adults were sampled from spawning tributaries, primarily in spring, and to a lesser extent in fall. Fish of domestic origin comprised ~80% of rainbow trout sampled from sites near cage culture facilities but <20% of rainbow trout sampled from more distant sites. Domestic adults in spawning condition (gametes free‐flowing) were present in the spawning tributaries in both spring and fall sampling seasons, whereas naturalised fish in spawning condition were only observed in the spring. Domestic adults were younger and smaller (in length), appeared to have shorter lifespan and had a higher male to female ratio compared with their naturalised counterparts. Growth rates (change in length with age) of naturalised and domestic females in the wild were similar, but domestic males grew more slowly than naturalised males. Domestic females also produced smaller eggs than naturalised females. Food web positions (inferred from δ13C and δ15N) of domestic and naturalised fish were very similar but varied more strongly with body size in the former. Domestic‐strain rainbow trout of cage culture origin can survive, grow and attempt to spawn in northern Lake Huron and have the potential to compete for food, mates and spawning habitat with naturalised rainbow trout.